Efektivitas Waktu Pengeringan Udara Alamiah terhadap Kualitas Sarang Semut (Myrmecodia tuberosa) Menggunakan Tipe Pengeringan Batch Dryer - Junita Magdalena Seuk; Jefrianus Nino; Maria Angelina Tuas (Fakultas Pertanian, Universitas Timor, 2022)
Ant nest (Myrmecodia tuberosa) is one of the plants that which contains flavonoids, tannins and polyphenols which functions as an antioxidant. One of the post-harvest handling technologies in maintaining the quality of the material that is drying. In the area of Timor natural air very potential in the drying process, because it is environmentally friendly and free. This study aims to determine the effectiveness of time natural air drying on the quality of ant nests using batch dryer drying and knowing the content of phytochemical compounds (flavonoids and tannins). This research is an experimental research designed using a single factor Completely Randomized Design with time variable drying (A) which consists of 3 levels, namely the drying time of 5 hours (A1), 10 hours (A2) and 15 hours (A3) and repeated 2 times so that there are 6 units treatment. Drying is carried out with a thickness of 2 mm. slices of ant nests mm. Determination of flavonoid content and tannin content was determined by the method quantitative. Based on the results of the study, 10 hours of drying produced levels of The highest flavonoid was 45.59 mg/g and the tannin content was 94.29 mg/g with the final water content is 26.04% bw. The content of phytochemicals (flavonoids and tannins) in ant nests, namely before drying with flavonoid content of 42.59 mg/g, 5 drying hours with 33.59 mg/g flavonoid content, 10 hours drying with flavonoid content of 45.06 mg/g and at 15 hours of drying with a concentration of flavonoids 20.42 mg/g.The tannin content before drying was 106.88 mg/g, 5 hours of drying with a tannin content of 74.55 mg/g, 10 hours of drying with tannin content was 94.29 mg/g, and at 15 hours of drying it was 92.62 mg/g.